Anthropometry, bone mineral density and risk of breast cancer in premenopausal and postmenopausal Saudi women - Nora AlFaris; Nora AlKehayez; Fatema AlMushawah; AbdulRhman AlNaeem; Nadia AlAmri; Ebtisam AlMudawah (Archives of Medical Science, 2020)
Introduction Anthropometry and bone mineral density are linked to hormonal imbalance, which plays a possible role in breast carcinogenesis. The current study was designed to explore the relationship between selected anthropometric and bone mineral density parameters and the risk of breast cancer in premenopausal and postmenopausal Saudi women.